The Contestation of the Prohibition of Tabarruj on Indonesian Social Media: A Virtual Ethnography Approach on Instagram - Mukaromah, Kholila; Rahayu, Siti; Munirah, Munirah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
In the digital era, discussions on the prohibition of tabarruj for women frequently appear in digital content, responding to women’s active presence in both real and virtual public spheres, and are variously addressed on social media. This article examines the contestation of the tabarruj prohibition in social media, especially on Instagram, based on the presentation of content, meaning, and acceptance among Indonesian Muslims. The research is included in media text studies about living Qur’an-Hadith on social media. The virtual ethnography method is used to collect data in digital space, especially on the Instagram platform for five accounts: @khalidbasalamahofficial, @humairahijab, @fikihmuslimah, @akhiukhtiantiselfie, and @mubadalah.id. Based on social media searches, the prohibition of tabarruj in these accounts is mostly based on QS. Al-Ahzab [33]: 33, the Prophet's hadith, and the views of Islamic scholars. Four of the contents present the prohibition of tabarruj specifically for women, and one content, @mubadalah.id, offers a new reading that tabarruj can be intended for both women and men. Readers more widely reach based on the influence of the content, @khalidbasamahofficial and @ukhriakhiantiselfie accounts, and @mubadalah.id accounts have fewer responses. Instagram, in this case, has become a medium for constructing religious discourse, both among followers of Salafism and supporters of the gender equality and justice movement in Indonesia. The significance of this research shows how the prohibition of tabarruj is understood, accepted, implemented, and even debated in the context of social media in Indonesia and has implications for contemporary religious understanding and practice.